Effectiveness of lifestyle modification on health-related quality of life among women with polycystic ovary syndrome - Asmaa Abobakr Ibrahim; Hanan M Ghoneim; Noha M Abu Bakr Elsaid; Nagat Salah Shalaby (Wolters Kluwer Medknow Publications, 2023)
Background: Polycystic Ovary Syndrome (PCOS) is the most common reproductive endocrine disorder, which affects approximately one in every five women at the age of reproduction. The first line of PCOS management is recommended to be lifestyle modification. This study aimed to evaluate the effectiveness of lifestyle modification on Health-Related Quality of Life (HRQoL) among women with PCOS. Materials and Methods: This quasi-experimental study was conducted on 124 women with PCOS recruited from the outpatient clinic at El-Takhassosy Obstetrics Hospital, Port-Said, Egypt, in 2021 and allocated to two groups; an educational group (n = 62) and a control group (n = 62). For data gathering, two tools were used; an interviewing questionnaire for assessing the demographic characteristics and a standardized HRQoL questionnaire. Healthy lifestyle modification educational sessions included nutritional guidelines for PCOS, physical exercise (walking for 30 min five times weekly), and instructions to relieve stress. Results: The mean (SD) of HRQoL score was 97.52 (8.75) in the educational group higher than the control group 87.32 (18.68) at 3 months postintervention and at 6 months postintervention; it reached 106.74 (11.53) in the educational group and 89.47 (22.14) in the control group. They were statistically significant after intervention (3 and 6 months) between studied groups (after 3 months was t86,563 = 3.891, p < 0.001 and after 6 months was t91,826. Conclusions: Women with PCOS should receive structured education about lifestyle modification next to treatment to ensure improvement, particularly in patient-centered care.